Bilingualism - Ila Amalia (English Education Department, 2017)
In most common definition a bilingual is a person who is able to speak and understand two languages. Most of us consider bilingualism as something good, an advantage. For one thing, knowledge of another language enables people to communicate with members of other cultures in their own language. This, in turn, provides a means for furthering cooperation and understanding among nations and peoples. Then rise some questions considering bilingualism such as: Is it a good idea to become a bilingual? Just what is a bilingual? Should a young child learn a second language? When should that be? How might learning a second language be affected by the first? These are questions which people and scientists commonly raise. This literature-based article will attempt to provide answers that offer some insight into these questions and other issues related to bilingualism.